(untitled) - Armstrong, Gary; Opresnik, Marc O (London, 2017)
Includes bibliographical references and indexes; An Introduction to the World of Marketing Using a Proven, Practical, and Engaging Approach, Marketing: An Introduction shows students how customer value—creating it and capturing it—drives every effective marketing strategy. Using an organization and learning design that includes real-world examples and information that help bring marketing to life, the text gives readers everything they need to know about marketing in an effective and engaging total learning package.
Keywords: Marketing; Tiếp thị